(untitled) - Pearce, M. J. (Wallingford, UK, 1997)
This book provides a general scientific introduction to termites, including their biology, behavior, pest status, and control. It is directed to advanced students in entomology and pest management, as well as to professionals."--Entomological News "Termites are among the most intriguing and important insects in the world. . . . Because of their unique capabilities as effective decomposers of cellulose, termites are essential in refueling many ecosystems by recycling vegetative nutrients to soils, but their appetite for wood also renders them structural pests worldwide . . . the author takes on the ambitious but engaging task of surveying both the biology and control of this diverse and captivating order of insects. . . . The strength of the book is its presentation of a large number of fascinating facets of termite biology . . . The diagrams are typically clear and useful, the tables are effectively compiled . . . , and the photographs are well selected to complement the text. . . . Pearce's book . . . capably acquaints readers with the diversity and wonder of termites, and provides an introduction of how to cope with them as structural pests."--The Quarterly Review of Biology
Keywords: Termites; Control